The Role of Arabinogalactan Type II Degradation in Plant-Microbe Interactions - Villa-Rivera, Maria Guadalupe; Cano-Camacho, Horacio; López-Romero, Everardo; Zavala-Páramo, María Guadalupe (Frontiers in Microbiology, 2021)
Arabinogalactans (AGs) are structural polysaccharides of the plant cell wall. A small proportion of the AGs are associated with hemicellulose and pectin. Furthermore, AGs are associated with proteins forming the so-called arabinogalactan proteins (AGPs), which can be found in the plant cell wall or attached through a glycosylphosphatidylinositol (GPI) anchor to the plasma membrane. AGPs are a family of highly glycosylated proteins grouped with cell wall proteins rich in hydroxyproline. These glycoproteins have important and diverse functions in plants, such as growth, cellular differentiation, signaling, and microbe-plant interactions, and several reports suggest that carbohydrate components are crucial for AGP functions. In beneficial plant-microbe interactions, AGPs attract symbiotic species of fungi or bacteria, promote the development of infectious structures and the colonization of root tips, and furthermore, these interactions can activate plant defense mechanisms. On the other hand, plants secrete and accumulate AGPs at infection sites, creating cross-links with pectin. As part of the plant cell wall degradation machinery, beneficial and pathogenic fungi and bacteria can produce the enzymes necessary for the complete depolymerization of AGs including endo-b-(1,3), b-(1,4) and b-(1,6)-galactanases, b-(1,3/1,6) galactanases, a-L-arabinofuranosidases, b-L-arabinopyranosidases, and b-D-glucuronidases. These hydrolytic enzymes are secreted during plant-pathogen interactions and could have implications for the function of AGPs. It has been proposed that AGPs could prevent infection by pathogenic microorganisms because their degradation products generated by hydrolytic enzymes of pathogens function as damage-associated molecular patterns (DAMPs) eliciting the plant defense response. In this review, we describe the structure and function of AGs and AGPs as components of the plant cell wall. Additionally, we describe the set of enzymes secreted by microorganisms to degrade AGs from AGPs and its possible implication for plant-microbe interactions.